Estilo de liderazgo y su influencia en la productividad de los servidores públicos de la Municipalidad Distrital de Chugay 2021 - Jara Ruíz, Jamin David (2022)
The attached study report was prepared in order to solve the formulated problem: In what way does the leadership style influence the productivity of public servants of the District Municipality of Chugay 2021?, It was emphasized in the formulated hypothesis: The Leadership style significantly influences productivity in public servants of the Chugay District Municipality 2021, for which the correlational, statistical descriptive design was applied; and a 38-item questionnaire was prepared for a sample of 75 municipal workers. The technique was the survey. Thus, it was concluded that there is an influence of both variables (0.805), demonstrating that leadership style is an elementary factor in public servants, since workers state that it allows them to have a good performance in their work. Likewise, all types of leadership taken for the present investigation are considered relevant to them. It was recommended that the Chugay District Municipality, through its manager, should continue to recommend to its heads of areas, continue to treat everyone well, good effective communication and above all, that it be participatory decisions, since that allows to have good productivity.